Multi‐omic dissection of the drought resistance traits of soybean landrace LX. (18th February 2021) - Zhao, Bing; Zhang, Shulin; Yang, Wenqi; Li, Bingyan; Lan, Chen; Zhang, Junli; Yuan, Li; Wang, Yu; Xie, Qiguang; Han, Jiwan; Mur, Luis A. J.; Hao, Xingyu; et al.
Abstract: With diverse genetic backgrounds, soybean landraces are valuable resource for breeding programs. Herein, we apply multi‐omic approaches to extensively characterize the molecular basis of drought tolerance in the soybean landrace LX. Initial screens established that LX performed better with PEG6000 treatment than control cultivars. LX germinated better than William 82 under drought conditions and accumulated more anthocyanin and flavonoids. Untargeted mass spectrometry in combination with transcriptomic analyses revealed the chemical diversity and genetic basis underlying the overall performance of LX landrace. Under control and drought conditions, significant differences in the expression of a suite of secondary metabolism genes, particularly those involved in the general phenylpropanoid pathway and flavonoid but not lignin biosynthesis, were seen in LX and William 82. The expression of these genes correlated with the corresponding metabolites in LX plants. Further correlation analysis between metabolites and transcripts identified pathway structural genes and transcription factors likely are responsible for the LX agronomic traits. The activities of some key biosynthetic genes or regulators were confirmed through heterologous expression in transgenic Arabidopsis and hairy root transformation in soybean. We propose a regulatory mechanism based on flavonoid secondary metabolism and adaptive traits of this landrace which could be of relevance to cultivated soybean. Abstract : The diverse genetic resources in soybean landraces could confer adaptive agricultural traits to certain regional stress conditions and could be utilized to accelerate breeding programs. However, few studies focus on the molecular basis of the stress resistances in soybean. In this work, we applied multi‐omic approach to dissect the genetic and metabolic basis of drought resistance in a soybean landrace LX. Combining transcriptome and metabolome analysis, we unraveled that enhanced phenylpropanoid metabolism, especially flavonoid metabolism, could be the key in LX resistance against drought. A suite of regulatory and biosynthetic genes were also functionally validated in either Arabidopsis or soybean. The results presented in this work pinpoint the significance of plant secondary metabolism in important agricultural traits and provide new targets for soybean breeding.